Malaysian hawker’s food image, food attributes satisfaction and behavioral intention in the perspective of Singapore tourist - Thew, Kok Lim (2015)
The purpose of this study was to determine the possibility of Malaysian gastronomic products specifically Malaysian hawker’s food as the centered motivation to travel to a place. A model was adapted to assess the Malaysian hawker’s food image, food attributes satisfaction and behavioral intention of the largest component of international tourists which was Singapore tourists. The results indicated that Malaysian hawker’s food possessed clear and positive images on “Food price”, “Delicious”, “Easy access” and “Well presented” but is rather unclear on the images of “Sufficiency of seats”, “Attractive eating surrounding”, “Variety of food choice”, “Many ethnic hawkers food” and “Use of herbs and spices”. Tourists were satisfied relatively higher on the elements of “Cultural experience” and “Price” but were relatively lower on the element of “Cleanliness and food safety”. In terms of intention, most of the items achieved an average mean score over 3.00 which indicated that the tourists did not have much negative perception and were relatively satisfied over Malaysian hawker’s food. Regression analyses revealed that food image and food attributes satisfaction were significantly predicted tourists’ behavioral intentions. The findings suggested that Malaysian hawker’s food can be upheld as unique Malaysian food and strengthens the notion of repeat visitation to savor Malaysian food. Practical and theoretical contributions are discussed, with future research suggested